Morphological and genetic characterization of Psenes cyanophrys Cuvier and Valenciennes, 1833 caught in Panay Gulf - Cabebe, Roxanne A. (2020.)
The two morphotypes of Psenes cyanophrys caught from Panay Gulf were investigated using morphological and genetic characters of the fish. A descriptive comparison of external and internal features using x-ray photographs between groups was identified. Eye diameter was the most distinguishable character; hence the samples were initially divided into two groups based on this character. The morphological variations were determined using two different morphometric methods. Traditional methods showed the linear measurements of 33 parameters while geometric morphometric methods quantity the shape variations from the 23 landmarks digitized in the images of fish. Both methods showed a significant difference; however, meristic counts in both groups are considerably similar. Both male specimens were observed in both groups thus, the study confirmed that variations in the morphology are not influenced by sex dimorphism. The result of the morphological analysis was not supported by the genetic character of the fish. Since only cytochrome oxidase subunit I (COI) was analyzed, the study recommends to further analyze the genetic characteristic of P. cyanophrys using nuclear gene markers.
Thesis (M.S. Fisheries Biology) -- [Maigao, Iloilo] : University of the Philippines Visayas, June 2020.
Keywords: Psenes cyanophyrs -- Morphological analysis